Prescribing emergency oral steroids in asthma clinics. Issue 10 (11th June 2019) - Willson, Rhian; Makhecha, Sukeshi; Moore-Crouch, Rachel; Balfour-Lynn, Ian M
Abstract : We retrospectively reviewed children who had been prescribed emergency oral corticosteroids (OCS) in a routine tertiary paediatric respiratory clinic appointment. We subsequently assessed adherence from prescription uptake of inhaled corticosteroids or combination inhalers in the 6 months prior to the episode. In 2 years, 25 children received 32 courses of prednisolone. Median adherence was 33%, but 28% for those with repeated OCS prescriptions. Prescribing acute OCS in a routine clinic is a red flag for potential poor adherence to preventer therapies, and may also indicate the child has poor perception of the severity of their symptoms. An assessment of adherence should be carried out and help given to the child and their family to improve poor adherence when detected.